Centaurus A as a plausible source of ultra high energy cosmic rays registered by the Pierre Auger Observatory - Sushchov, O.B.; Kobzar, O.O.; Hnatyk, B.I.; Marchenko, V.V. (Advances in Astronomy and Space Physics, 2012)
For ultra high energy cosmic rays events detected by the Pierre Auger Observatory which arrive from the region near Centaurus A the positions of the corresponding sources were calculated for the two chosen galactic magnetic field models. Also the influence of extragalactic magnetic field was taken into account for different energy and ultra high energy cosmic rays type to show the possibility of correlation with Centaurus A.